Functional response of Neoseiulus californicus (Acari: Phytoseiidae) to Tetranychus urticae (Acari: Tetranychidae) at different temperatures - Mumtaz,Maryam; Rahman,Vattakandy Jasin; Saba,Tahseen; Huang,Tingting; Zhang,Yuxin; Jiang,Chunxian; Li,Qing (PeerJ, 2023)
Environmental factors like temperature have a great impact on the predation potential of biological control agents. In the present study, the functional response of the predatory mite Neoseiulus californicus (Acari: Phytoseiidae) to the pest mite Tetranychus urticae (Acari: Tetranychidae) at moderate to high temperatures under laboratory conditions was determined. The study aimed to understand the prey-predator interaction under different temperatures and prey densities. Five constant temperatures (24 °C, 27 °C, 30 °C, 33 °C, and 36 °C), and thirteen prey densities (4, 5, 8, 10, 12, 15, 16, 20, 24, 25, 30, 32, and 40) of each stage (adult, nymph, larvae, and egg stage) were employed in the experiment. Observations were made 24 h after the start of each experiment. Results revealed that the predatory mites showed type II functional response to adult females of T. urticae, whereas type I to other stages (nymphs, larvae, and eggs) of T. urticae. The predation capability of adult predatory mites on T. urticae was significant at 24–36 °C. The instantaneous attack rate (a) of N. californicus increased and the handling time (Th) decreased with an increase in temperature. The maximum attack rate was recorded at 36 °C (1.28) for the egg stage. The longest handling time was (0.78) for the larval stage of T. urticae at 30 °C. Daily consumption increased with increasing prey density. Maximum daily consumption was observed at 33 °C (30.00) at the prey density of 40. Searching efficiency decreased with the increase in prey density but was found to increase with the rise in temperature. N. californicus was found to be voracious on the larval and egg stages. Conclusively, the incorporation of N. californicus at earlier stages (larvae and eggs) of T. urticae would be beneficial under warm conditions because managing a pest at its initial stage will save the crop from major losses. The results presented in this study at various temperatures will be helpful in different areas with different temperature extremes. The results of the functional response can also be applied to mass rearing, quality testing, and integrated pest management programmes.
Keywords: Neoseiulus californicus; Tetranychus urticae; Phytoseiidae; Functional response; Biological control